Excitotoxicity and oxidative damages induced by methylmercury in rat cerebral cortex and the protective effects of tea polyphenols. Issue 3 (5th January 2012) - Liu, Wei; Xu, Zhaofa; Deng, Yu; Xu, Bin; Yang, Haibo; Wei, Yangang; Feng, Shu
<x xml:space="preserve">Abstract</x> Methylmercury (MeHg) is a highly neurotoxic environmental pollutant that has a high appetency to the central nervous system. The underlying mechanisms of MeHg‐induced neurotoxicity have not been elucidated clearly until now. Therefore, to explore the mechanisms contribute to MeHg‐induced neurotoxicity, rats were exposed to different dosage of methylmercury chloride (CH3ClHg) (0, 4, and 12 μmol kg−1) for 4 weeks to evaluate the neurotoxic effects of MeHg. In addition, considering the antioxidative properties of tea polyphenols (TP), 1 mmol kg−1 TP was pretreated to observe the possible protective effects on MeHg‐induced neurotoxicity. Then Hg, glutamate (Glu) and glutamine (Gln) levels, glutamine synthetase (GS), phosphate‐activated glutaminase (PAG), Na+‐K+‐ATPase, and Ca2+‐ATPase activities, intracellular Ca2+ level were examined, glutathione (GSH), malondialdehyde (MDA), protein sulfhydryl, carbonyl, 8‐hydroxy‐2‐deoxyguanosine (8‐OHdG), and reactive oxygen species (ROS) levels, N‐methyl‐D‐aspartate receptors (NMDARs) mRNA and protein expressions, apoptosis level and morphological changes in the cerebral cortex were also investigated. Study results showed that compared with those in control, exposure to CH3ClHg resulted in excitotoxicity in a concentration‐dependent manner, which was shown by the Glu‐Gln cycle disruption and intracellular Ca2+ homeostasis disturbance. On the other hand, CH3ClHg exposure resulted in oxidative damages of brain, which were supported by the significant changes on GSH, MDA, sulfhydryl, carbonyl, 8‐OHdG, and ROS levels. Moreover, apoptosis rate increased obviously and many morphological changes were found after CH3ClHg exposure. Furthermore, this research indicated that TP pretreatment significantly mitigated the toxic effects of MeHg. In conclusion, findings from this study indicated that exposure to MeHg could induce excitotoxicity and oxidative damage in cerebral cortex while TP might antagonize the MeHg‐induced neurotoxicity. © 2012 Wiley Periodicals, Inc. Environ Toxicol 29: 269–283, 2014.